1993
DOI: 10.2527/1993.7182228x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding value of wet distillers byproducts for finishing ruminants

Abstract: Yearling and calf finishing trials (replicated over 2 yr) evaluated the feeding value of wet distillers byproducts (wet distillers grains and thin stillage). An additional trial estimated the amount of thin stillage bypassing the rumen when consumed by drinking. Yearlings were 5, 10, and 20% more efficient (linear, P < .01; quadratic, P = .05), whereas calves were 2, 6, and 14% more efficient (linear, P < .01) when fed 5.2, 12.6, and 40.0% (DM basis) wet distillers byproducts, respectively, compared with cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
122
13

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(152 citation statements)
references
References 23 publications
17
122
13
Order By: Relevance
“…Cattle fed corn DDGS exhibited (P B0.01) a quadratic increase in gain:feed (y 00.1564 (0.0003x'0.00003x 2 R 2 00.95 SEP 0.004) with a local minima at the 4.6% inclusion level. These results support Larson et al (1993) who reported cattle fed corn WDGS at 40% of the ration had a 20% improvement in gain:feed. Ham et al (1994) also reported similar results for both corn WDGS and DDGS.…”
Section: Finishing Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…Cattle fed corn DDGS exhibited (P B0.01) a quadratic increase in gain:feed (y 00.1564 (0.0003x'0.00003x 2 R 2 00.95 SEP 0.004) with a local minima at the 4.6% inclusion level. These results support Larson et al (1993) who reported cattle fed corn WDGS at 40% of the ration had a 20% improvement in gain:feed. Ham et al (1994) also reported similar results for both corn WDGS and DDGS.…”
Section: Finishing Performancesupporting
confidence: 89%
“…With regards to feedlot cattle, there has been a significant amount of research on the feeding value of corn-based DDGS as both a protein and energy source, and its associated effects on carcass traits (Ham et al 1994;Klopfenstein et al 2008). In terms of the energy value of corn distillers' grains with solubles, Larson et al (1993) observed that wet distillers' grains with solubles (WDGS) when fed at levels ranging from 5.2 to 40% of DM averaged 2.53 and 1.96 Mcal kg(1 NE g , when fed to yearlings and calves, respectively. These values averaged 169 and 128% the NE g value of dry rolled corn.…”
mentioning
confidence: 99%
“…Dietary net energy was calculated using iterations based on tabular energy values and measured lamb performance (DMI and ADG) following the system described by Larson et al (1993) with modifications made with respect to species (NRC, 1985). Lamb net energy requirements (Mcal per day) for maintenance (NE m R) and gain (NE g R) were calculated using equations: NE m R = 0.056×BW 0.75 and NE g R = 0.276× BW 0.75 ×ADG (NRC, 1985), where average BW (kg) and ADG (kg per day) during the experiment were used.…”
Section: Calculations Measurements and Statisticsmentioning
confidence: 99%
“…Owing to the chemical composition of the dry matter basis (Table 2) (but primarily because of the beneficial proportion of the total protein content to the contents of the other nutrients) potato stillage has been regarded as valuable fodder (despite high water content, 90 to 95.3%) (Maiorella et al 1983;Larson et al 1993;Ham et al 1994;Fisher et al 1999;Mustafa et al 2000). It should, however, be noted that the feeding value of the potato stillage (determined as protein and vitamin content) is lower than that of the grain stillage (Maiorella et al 1983).…”
Section: Methods Of Stillage Utilizationmentioning
confidence: 99%